2017
DOI: 10.1016/j.tjem.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of Emergency Medical Services demand: Time of day, day of the week, and location in the city

Abstract: ObjectiveEffective planning of Emergency Medical Services (EMS), which is highly dependent on the analysis of past data trends, is important in reducing response time. Thus, we aimed to analyze demand for these services based on time and location trends to inform planning for an effective EMS.Materials and methodsData for this retrospective study were obtained from the Izmir EMS 112 system. All calls reaching these services during first six months of 2013 were descriptively analyzed, based on time and location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
0
13
0
11
Order By: Relevance
“…The number of calls for communicable disease reached 12,884 from 1 March to 23 April 2020. This surge in calls likely relates to the following: (i) An increase in suspected COVID-19 cases due to new guidelines for classifying any patient with cough or fever as infectious, and (ii) fear of transporting patients with fever, cough, or other symptoms of COVID-19 in personal vehicles leading to an increase in calls to EMS for an ambulance [ 16 ]. Saudi Arabia has a high proportion of EMS calls for trauma due to motor vehicle collisions [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of calls for communicable disease reached 12,884 from 1 March to 23 April 2020. This surge in calls likely relates to the following: (i) An increase in suspected COVID-19 cases due to new guidelines for classifying any patient with cough or fever as infectious, and (ii) fear of transporting patients with fever, cough, or other symptoms of COVID-19 in personal vehicles leading to an increase in calls to EMS for an ambulance [ 16 ]. Saudi Arabia has a high proportion of EMS calls for trauma due to motor vehicle collisions [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 Previous studies have shown that high population densities and high proportions of females and elderly people lead to higher EMS utilizations. 15,21,22 Residences in high-rise buildings have longer EMS response times. 23 Therefore, the proportion of apartments in the area was included in the analysis to assess its association with EMS utilizations.…”
Section: Outcomes and Measurementsmentioning
confidence: 99%
“…Our intention a priori in this study was to identify if weather-related variables were potential predictors of EMS demand after accounting for other factors known to affect the timing of EMS responses. As such, we included weekend/weekday status in our model as this variable has been specifically known to be associated with EMS demand (25,26).…”
Section: Weather Datamentioning
confidence: 99%